Relationships in a Family with High Academic Achievement Students - Sylwia Gwiazdowska-Stańczak (Jesuit University Ignatianum in Krakow, 2020)
RESEARCH OBJECTIVE: School achievements are an important dimension of human life and are conditioned by internal and external factors, to which family belongs. The purpose of this investigation was to answer the question how of high academic achievement students perceive their relationships in the family. THE RESEARCH PROBLEM AND METHODS: The Family Questionnaire was used in the version "My Family, My Father and My Mother," developed by Plopa and Połomski. The subjects were 16 year-old students (n = 155), who achieved high scores in the lower secondary school test, and a comparative group with the average score (n = 161). THE PROCESS OF ARGUMENTATION: The students assessed relationships in their families in terms of the following dimensions: communication, cohesion, identity and autonomy-control. RESEARCH RESULTS: It was found that for students with high school performance, cohesion in relation to father is more important than for the comparative group. CONCLUSIONS, INNOVATIONS, AND RECOMMENDATIONS: In addition, it was found that there are differences in the perception of family relationships on the basis of the gender of the studied students. Boys assessed cohesion and communication with their father on a higher level than girls. An interesting result of the study is a higher assessment of family identity in the perceptions of boys than girls.